Biological Effects and Biomedical Applications of Areca Nut and Its Extract - Ting Tong; Aiqing Xu; Shuhua Tan; Hengzhi Jiang; Lixin Liu; Senwen Deng; Haihua Wang (Pharmaceuticals, 2024)
The dried, mature fruit of the palm tree species Areca catechu L. is known as the areca nut (AN) or betel nut. It is widely cultivated in the tropical regions. In many nations, AN is utilized for traditional herbal treatments or social activities. AN has historically been used to address various health issues, such as diarrhea, arthritis, dyspepsia, malaria, and so on. In this review, we have conducted a comprehensive summary of the biological effects and biomedical applications of AN and its extracts. Initially, we provided an overview of the constituents in AN extract. Subsequently, we summarized the biological effects of AN and its extracts on the digestive system, nervous system, and circulatory system. And we elucidated the contributions of AN and its extracts in antidepressant, anti-inflammatory, antioxidant, and antibacterial applications. Finally, we have discussed the challenges and future perspectives regarding the utilization of AN and its extracts as emerging pharmaceuticals or valuable adjuncts within the pharmaceutical field.